Corporate social performance in family firms: a meta-analysis. Issue 3 (10th August 2018) - Canavati, Sergio
Abstract : Purpose: Empirical studies provide conflicting conclusions regarding the corporate social performance (CSP) of family firms. The purpose of this paper is to synthesize the existing empirical evidence and examine the potential role of research design and contextual factors. Design/methodology/approach: A meta-analysis of existing empirical studies was performed to examine the role of sampling, measurement and contextual factors in explaining the different and often conflicting results of empirical studies in the family business literature. Findings: The overall relationship between family firms and CSP is positive. The relationship between family firms and CSP is positive for private family firms but is negative for public family firms. The relationship between family firms and CSP is positive when family involvement includes both family ownership and management as opposed to only family ownership or family management. Private family firms care more and public family firms care less about the community, environment, and employees than private and public nonfamily firms. The relationship between family firms and CSP is stronger in institutional environments with weak labor and corporate governance regulatory frameworks. Research limitations/implications: The operationalization of both the family firm and CSP constructs significantly predicts the magnitude and direction of the relationship between family firms and CSP. Practical implications: Family firms should become more skilled at measuring and disseminating information about the firm's CSP. Family firms should work to improve public perceptions about the CSP of family firms. Social implications: Policy should encourage family firms to remain privately owned by the family. Policy should also incentivize the involvement of family owners in the management of family firms. Originality/value: Although several literature reviews address the relationship between family firms and CSP, this is the first review to use the meta-analysis method. The authors contribute to the family business literature by analyzing how differences in study-, firm- and country-level factors can explain some of the variance in the results of the studies in the literature.